Attention-deficit/hyperactivity disorder (ADHD) in adults: a multilayered approach to a serious disorder of inattention to the future - André Palmini (Arquivos de Neuro-Psiquiatria)
Attention-deficit/hyperactivity disorder (ADHD) affects people of all ages, yet its presentation varies as the person matures and social demands increase from childhood into adulthood. Interestingly, when analyzing the disorder in adults, it is not immediately clear what the ‘attention deficit’ in the ADHD denomination exactly means. Adults with ADHD have a broad range of difficulties, far beyond an attentional deficit, that impact negatively their social functioning and often lead to failures in all walks of life. Therefore, in this review, I attempt to reconcile the notion of attention deficit with the protean manifestations of ADHD in adults through a proposal that ADHD symptoms have as a common denominator an inattention to the future. I build this construct through a multilayered approach, progressing from the epidemiological and clinical considerations for Diagnostic and Statistical Manual of Mental Disorders (DSM) diagnosis, to a deeper understanding of the disorder, discussing how these patients fail to anchor the present into the future (i.e., to be attentive to future consequences), thus failing to approximate future goals from present action. Integrating cognitive observations with imaging abnormalities, it is possible to propose that ADHD in adults is perhaps the most prevalent frontal lobe disorder in humans, ultimately impacting upon psychosocial management and treatment strategies.